Managing obesity in pregnancy. (7th June 2011) - Navaratnam, K; Akhtar, M; Davies, M
Abstract : Aims: To identify the proportion of obese women booking for obstetric care. Audit compliance with local and CMACE guidance, 1 and assess labour outcomes for these women. Background: Maternal obesity is a common obstetric risk factor, with 4.99% UK prevalence.2 A body mass index (BMI) ≥35 confers moderate obstetric risk, a BMI≥40 confers high obstetric risk.2 In the 2003–2005 CEMACH report, 28% of mothers who died were obese.3 A pregnancy complicated by obesity increases the risk of preeclampsia, gestational diabetes mellitus (GDM), dysfunctional labour, operative intervention and postpartum haemorrhage 2. Methods: A 12-month retrospective case-note audit of women booking with a BMI≥35. Results: 62 women identified with a BMI≥35, 34 women had a BMI≥40. 76% had an anaesthetic review, 94% had a glucose tolerance test, 69% had fetal growth estimated by ultrasound. 79% of women laboured, 35% of labours were induced. 60% of women had a normal delivery, 6% had instrumental delivery, 15% had an emergency caesarean section (CS), 19% had an elective CS. 29% had an estimated blood loss ≥500 ml at delivery. Venous thromboembolic (VTE) risk was poorly assessed, with insufficient thromboprophylaxis for weight. Antenatally, no women had high VTE risk, 21% had intermediate risk. Postnatally 5% had high VTE risk, 71% had intermediate risk. Conclusion: Pre-pregnancy and antenatal risk counselling is vital, with surveillance for preeclampsia in addition to GDM. Standardised VTE risk assessment should be introduced, with weight-appropriate thromboprophylaxis. Normal birth should be promoted, to reduce obstetric interventions in this high risk group.